Strategy for Improving Military Human Resource Competence in the Era of Artificial Intelligence: Conceptual and Policy Review - Septian, Alif; Khomariah, Sinta (Universitas Pattimura, 2025)
The rapid development of artificial intelligence (AI) in the defense sector demands a fundamental transformation in military human resource (HR) competency strategies. This conceptual and policy review aims to identify key competency domains for AI-enabled military forces, map global policy responses, and formulate an integrated development strategy for the Indonesian context. Through thematic synthesis of 112 scholarly articles (2015–2025) and 18 international defense policy documents, the study identifies three mutually reinforcing competency clusters: technical–algorithmic literacy, adaptive cognitive and teamwork skills, and ethical–legal judgment. These are structured within the Military AI Competency Model (MAICM), which comprises four maturity levels. International benchmarking shows that countries such as the United States, NATO members, and Singapore have developed dual-track education (technical and ethical), rapid experimentation environments (sandboxing), and multisector talent ecosystems. In contrast, Indonesia’s defense HR policy remains fragmented across branches, lacks depth in competencies, and overlooks ethical and cross-domain data governance dimensions. To address these gaps, the study proposes the 3-E Strategy—Education, Experimentation, Ecosystem—which includes AI-integrated curricula, joint innovation labs, and military–academic–industry exchange programs. This study’s novelty lies in its holistic approach, combining HR development theory with defense policy analysis, and its integrative model aligning competency building with organizational culture and civil–military relations—contributing to social sciences and humanities through ethical AI education, iterative policy evaluation, and institutional reflexivity.